2017
DOI: 10.1002/hed.24961
|View full text |Cite
|
Sign up to set email alerts
|

Risk of depressive disorder among patients with head and neck cancer: A nationwide population‐based study

Abstract: Patients with head and neck cancer had >3 times the incidence of depressive disorder, relative to the comparison group. Psychological evaluation and support are essential in head and neck cancer survivors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
44
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 25 publications
(45 citation statements)
references
References 30 publications
1
44
0
Order By: Relevance
“…In total 33 of these articles fulfilled the eligibility criteria. In addition, two studies were included after screening the reference lists, resulting in 35 articles . These 35 articles provided results on 27 separate studies.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…In total 33 of these articles fulfilled the eligibility criteria. In addition, two studies were included after screening the reference lists, resulting in 35 articles . These 35 articles provided results on 27 separate studies.…”
Section: Resultsmentioning
confidence: 99%
“…In Table , the characteristics of the 35 included studies are described. Twenty‐one studies reported on factors associated with depression at a single time point, 10 studies on factors associated with the course of depression and four on both . Results on factors associated with depression at a single time point and the course of depression are presented separately.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations